(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2023)
The current study examined the effect of ginger extract (zingiber officinale aqueous and alcoholic) on a number of bacterial isolates. The tests showed a similar effect between the aqueous and alcoholic ginger extract on the tested bacterial species. All bacterial species used were resistant to concentrations of 3% and 6% for both alcoholic and aqueous extracts. It also proved close inhibition effectiveness of the aqueous extract on all bacterial species at a concentration of 12%, where the inhibition diameter was 14 mm on both Escherichia coli and Staphylococcus aureus, while the inhibition diameter was 15 mm on Klebsiella pneumonia. As for the alcoholic extract, it had a similar effect on Klebsiella pneumonia and Staphylococcus aureus, where the inhibition diameter reached 16 and 15 mm, respectively, while it had less effect on Escherichia coli, where the inhibition diameter reached 12 mm. Escherichia coli bacteria showed resistance to both extracts at a concentration of 9%, while the aqueous extract of this concentration had an inhibitory effect on Klebsiella pneumonia and Staphylococcus aureus with an inhibition diameter of 8 and 9 mm, respectively, while the alcoholic extract was equal in its effect on them with an inhibition diameter of 11 mm each.